2012
DOI: 10.5114/ninp.2012.31355
|View full text |Cite
|
Sign up to set email alerts
|

Serum S100B protein: a useful marker in obstructive sleep apnea syndrome

Abstract: Serum S100B protein level is increased in patients with OSAS and may be a useful biochemical marker in those patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…The circulating levels of VEGF are frequently increased in OSA patients and play a role in the regulation of tissue oxygen delivery [22,28]. The levels of IL-8 have been reported to be higher in OSA patients than those in healthy controls [16,29], while the S100B levels are increased in OSA patients but do not correlate with the severity of the disease [24,30]. We only observed increased levels of VCAM-1 and moderate increased levels of VEGF, which may be due to the differences between the populations since our cohort included patients with cutaneous melanoma and OSA; the cutaneous melanoma effect, that is independently related with the increase of VEGF [31,32], together with IL-8 [28,32], ICAM-1 [18,33], S100B [7,34,35] and MIA [7,35,36], could mask the OSA effect on these proteins, which may explain why we did not observe the previously reported differences in these biomarkers in the patients with OSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The circulating levels of VEGF are frequently increased in OSA patients and play a role in the regulation of tissue oxygen delivery [22,28]. The levels of IL-8 have been reported to be higher in OSA patients than those in healthy controls [16,29], while the S100B levels are increased in OSA patients but do not correlate with the severity of the disease [24,30]. We only observed increased levels of VCAM-1 and moderate increased levels of VEGF, which may be due to the differences between the populations since our cohort included patients with cutaneous melanoma and OSA; the cutaneous melanoma effect, that is independently related with the increase of VEGF [31,32], together with IL-8 [28,32], ICAM-1 [18,33], S100B [7,34,35] and MIA [7,35,36], could mask the OSA effect on these proteins, which may explain why we did not observe the previously reported differences in these biomarkers in the patients with OSA.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic inflammation due to hypoxia-reoxygenation cycles in OSA may activate diverse physiopathological pathways that enhance tumour progression [14,15]. Both diseases are associated with elevated circulating levels of adhesion molecules, such as intercellular adhesion molecule (ICAM)-1 [16][17][18] and vascular cell adhesion molecule (VCAM)-1 [17,19,20]; inflammation cytokines, such as vascular endothelial growth factor (VEGF) [21,22] and interleukin (IL)-8 [7,16,23]; and biomarkers of the prognosis and severity of melanoma, such as S100 calcium binding protein B (S100B) [7,24] and melanoma inhibitory activity (MIA) [7].…”
Section: Introductionmentioning
confidence: 99%
“…The studies were published from 2002 to 2017. Two studies were reported in Germany [10,21], two in Brazil [15,17], one in the Czech Republic [16], three in Turkey [18][19][20], and one in Egypt [22]. Three were crosssectional studies [10,16,17], and six were casecontrol studies [15,[18][19][20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the S100B level was not significantly correlated with OSAS severity. Several studies [15,[19][20][21][22] reported higher serum S100B levels in OSAS patients than in the controls, indicating a significant difference in four studies [15,19,21,22]. Two studies [15,18] showed that the serum NSE level was significantly in OSAS patients higher than in the controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation